1978
DOI: 10.1097/00000658-197804000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Rubber Band Seton in the Management of Abscess-Anal Fistula

Abstract: An elastic seton has been used in more than 35 patients in the surgical management of anterior abscess-anal fistula and anterolateral anal fistula in women. Elastic setons are applicalbe in the treatment of other complicated abscess-anal fistulas. The advantage of this method is the good functional result, with a minimal deformity of the anus. The treatment can be administered with a minimal number of hospital days or, in some instances, on an outpatient basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 0 publications
1
25
0
1
Order By: Relevance
“…22 After the suppuration has subsided, the rubber band is tightened with serial sutures or a hemorrhoidal ligator every 2 weeks until the rubber band Seton cuts through the muscle completely. 23 In a small series, a cutting seton was associated with low recurrence rates (0.8%) and minor incontinence (2-6%) and major incontinence of 5-10%. 24 Using a chemical seton, a seton coated with latex is impregnated with Kshara, an alkaline compound, and is introduced in the fistula tract and tightened progressively, allowing the chemical to cut through the fistula and allowing the tissue to reunite behind the cutting seton.…”
Section: Fistulotomy With Sphincterotomymentioning
confidence: 88%
See 1 more Smart Citation
“…22 After the suppuration has subsided, the rubber band is tightened with serial sutures or a hemorrhoidal ligator every 2 weeks until the rubber band Seton cuts through the muscle completely. 23 In a small series, a cutting seton was associated with low recurrence rates (0.8%) and minor incontinence (2-6%) and major incontinence of 5-10%. 24 Using a chemical seton, a seton coated with latex is impregnated with Kshara, an alkaline compound, and is introduced in the fistula tract and tightened progressively, allowing the chemical to cut through the fistula and allowing the tissue to reunite behind the cutting seton.…”
Section: Fistulotomy With Sphincterotomymentioning
confidence: 88%
“…2 Buie reported an incidence of 5% anal fistulas in those with anorectal abscess seen at the Mayo Clinic. 3 Using operating room data in Helsinki, Finland (1969-1978, the incidence of fistula was calculated to be 8.6 per 100,000 population per year (12.3% males and 5.6% females). 4 Nelson is his meta-analysis equated this with 20,000 to 25,000 fistulas treated annually in the United States.…”
Section: Incidencementioning
confidence: 99%
“…There are cutting, loose, and chemical setons. A cutting seton may be preferred when not all the sphincter is involved and a drainage seton if the tract passes deep to all of the sphincteric muscles [6, 7, 8]. …”
Section: Discussionmentioning
confidence: 99%
“…A prospective randomized trial by Ho et al [10], comparing ayurvedic cutting seton and fistulotomy for low fistula in ano, concluded that the chemical seton was more painful than conventional fistulotomy and there was no difference in time to wound healing, complications or functional outcome. Hanley [11] reported the use of a rubber-band seton in the surgical management of anterior abscess-anal fistulas and anterolateral fistulas in women with good functional results. Mentes et al [5] and Chuang-Wei et al [12] described the use of an elastic seton which was created by cutting a thin (2-3 mm) circular strip from a surgical glove, including its thicker sleeve.…”
Section: Variation In Seton Materialsmentioning
confidence: 99%